1642 Effect of Enterococcus fecalis SROD5 supplementation on microbial communities and quantities of in vitro rumen fermentation. (1st October 2016) - Mamuad, L. L.; Lee, S. S.; Biswas, A. A.; Jeong, C. D.
Abstract: Enterococcus fecalis is one of the beneficial microorganisms, which produces fumarate reductase that converts fumarate to succinate and reduces methane production in vitro. Hence, this study was conducted to determine the effect of E. fecalis SROD5 supplementation on archaeal diversity and microbial population. Fresh culture of E. fecalis SROD5 (7.5 × 10 8 cfu/ml) at different inclusion rates (0, 0.1%, 0.5%, and 1.0%) were investigated using in vitro rumen fermentation. Ruminal samples were collected from cannulated Holstein Friesian cow and 40:60 rice straw to concentrate ratio were used as substrate at 1 g dry matter (DM) per 100 ml buffered rumen fluid. Samples from in vitro fermentation of 12 h incubation were used for determination of microbial community and quantity. Pyrosequencing of archaeal 16S rRNA gene showed that the number of operational taxonomic units (OTU) was highest in supplementation of 0.1% E. fecalis SROD5 (39). Shannon-Weaver index were comparable among control and treatments while Chao 1 was higher in 0.1% and 0.5% supplementation of E. fecalis SROD5 with 52 and 54, respectively. Meanwhile, alignment of archaeal reads showed that almost all retrieved from in vitro rumen fermenta samples fell into the phylum Euryarchaeota, which predominantly affiliated with family Methanobacteriaceae (97% to 99%) followed by Methanomicrobiaceae, and Methanosarcinaceae . Abundance of Methanobrevibacter was higher in non-supplementation of E. fecalis SROD5 with 96.54%. Higher abundance of Methanomicrobium was observed in 0.1% E. fecalis SROD5 supplementation while higher abundance of Methanosphaera and unclassified Methanobacteriaceae as well as the presence of Methanimicrococcus were observed in 0.5% E. fecalis SROD5. Supplementation of 0.1% E. fecalis had the highest quantities of total bacteria (2.59 × 10 8 copies/ml), total fungi (1.03 × 10 4 copies/ml), Fibrobacter succinogenes (1.62 × 10 5 copies/ml), and Ruminococcus flavefaciens (1.51 × 10 3 copies/ml) while the highest methanogen quantity was observed in non-supplementation of E. faecium with 2.74 × 10 1 copies/ml). Addition of E. fecalis SROD5 changed the archaeal communities of in vitro rumen fermenta. Supplementation of 0.1% E. fecalis SROD5 increased microbial population and decreased methanogen quantity.